Biosurfactant as the next antimicrobial agents in pharmaceutical applications - Vello, Sumathy; Jamal, Parveen; Alam, Md Zahangir; S Noor, Mohammed SJ; Wan Nawawi, Wan Mohd Fazli (2019)
The number of patients with antimicrobial resistance is growing as a result of new emerging microbes or overuse of antibiotics. A new substitute to the existing antimicrobial agents is important in time to come to control the mortality rate in the global population. Natural substances, like biosurfactants or commonly known as microbial surfactants could be a potential antimicrobial agent to medical personnel’s consideration as some biosurfactants exhibits antimicrobial activity. Hence, this paper will briefly highlight some of the findings from contemporary researchers who have tested different biosurfactants for potential antimicrobial activity.